Method for manufacturing sheet for solid secondary battery, binder for solid secondary battery electrode, composition for producing electrode, electrode mixture, and electrode
By using a composition of polytetrafluoroethylene resin and conductive additive as a binder, and using spray drying and shear force imparting methods, the problems of high resistance and reduced strength of the secondary battery sheet are solved, and the low Resistance and high-strength electrode mixture are suitable for the formation of electrolyte layers in solid secondary batteries.
Patent Information
- Application Number
- CN202380050627.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-23
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the secondary battery sheet using PTFE as the binder is prone to problems of high resistance and reduced strength, and the uneven presence of active substances will affect the conductivity and mechanical strength of the electrode.
The composition using polytetrafluoroethylene resin and conductive additives as necessary ingredients is prepared to prepare powder binders without active substances, and the electrode mixture is obtained by spray drying and shear force imparting methods to reduce the resistance of the electrode. and increase its strength.
It is realized that the resistance value is reduced in the secondary battery sheet using PTFE, while improving the strength and conductivity of the electrodes, which are suitable for the formation of the electrolyte layer of the solid-state secondary battery.
Smart Images

Figure CN119487649A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for producing a sheet for a solid secondary battery, a binder for a solid secondary battery electrode, a composition for producing an electrode, an electrode mixture, and an electrode. Background Art
[0002] The use of fibrillated polytetrafluoroethylene (PTFE) as a binder in an electrode of a lithium ion battery containing a non-aqueous electrolyte is being studied (Patent Document 1).
[0003] Furthermore, it is disclosed that a uniform mixed powder obtained by mixing a conductive material and PTFE by spray drying is obtained (Patent Documents 2 to 4).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application No. 2017-517862
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 6-316784
[0008] Patent Document 3: Japanese Patent Application Publication No. 2008-140809
[0009] Patent Document 4: International Publication No. 2020 / 170797
[0010] Patent Document 5: Japanese Patent Application Publication No. 2020-115485 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The present disclosure aims to provide a method for producing a solid secondary battery sheet and a binder for a solid secondary battery, which can achieve low resistance of the sheet and obtain the strength of the composite sheet in a secondary battery sheet using PTFE.
[0013] Means for solving problems
[0014] The present disclosure relates to a method for producing a solid secondary battery sheet, characterized in that the method comprises the following steps: step (1), using a binder in which a polytetrafluoroethylene resin and a conductive auxiliary agent are uniformly mixed and which is a powder without containing an active material, to prepare a composition for producing a secondary battery sheet; and step (2), applying a shear force while mixing the composition for producing a secondary battery sheet to obtain an electrode mixture.
[0015] The step (2) is performed under the condition that the amount of solvent contained in the secondary battery sheet-forming composition is 10% by mass or less.
[0016] The content of the polytetrafluoroethylene resin in the electrode mixture is preferably 0.9 mass % or less.
[0017] The water content of the binder is preferably 1000 ppm or less.
[0018] The binder is preferably produced by a production method having a step (A) of mixing a polytetrafluoroethylene resin and a conductive additive in the presence of a liquid medium.
[0019] The above-mentioned liquid medium is preferably water.
[0020] The above-mentioned binder is preferably obtained by a production method having a step (B) of drying the composition obtained in the step (A) by spray drying.
[0021] The standard specific gravity of the polytetrafluoroethylene resin is preferably 2.130 to 2.200.
[0022] The secondary battery sheet-making composition preferably contains a positive electrode active material.
[0023] The secondary battery is preferably a lithium ion secondary battery.
[0024] The composition for producing a secondary battery sheet preferably has a fibrous structure in which the fibril diameter (median value) in the solid-state secondary battery sheet is 20 nm or more.
[0025] The binder preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.4 to 3.0 as measured by elemental analysis.
[0026] The present disclosure also relates to a binder for solid secondary battery electrodes, characterized in that it is composed of a composition having polytetrafluoroethylene resin and a conductive aid as essential components and is a powder that does not contain an electrode active material.
[0027] The polytetrafluoroethylene resin and the conductive additive are contained in a weight ratio of 90:10 to 65:35.
[0028] The water content of the binder is preferably 1000 ppm or less.
[0029] The binder preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.4 to 3.0 as measured by elemental analysis.
[0030] The present disclosure also relates to a binder for solid-state secondary battery electrodes, characterized in that it contains mixed powder of polytetrafluoroethylene resin and Ketjen black and / or carbon nanotubes.
[0031] The present disclosure also relates to a composition for preparing an electrode, characterized in that it contains the above-mentioned binder for solid-state secondary battery electrodes.
[0032] The present disclosure also relates to an electrode mixture, characterized in that it contains the above-mentioned binder for solid-state secondary battery electrodes.
[0033] The present disclosure also relates to an electrode, characterized in that it comprises the above-mentioned electrode mixture.
[0034] Effects of the Invention
[0035] The present disclosure can provide a method for producing a solid-state secondary battery sheet and a binder for a solid-state secondary battery, which can reduce the resistance value of the sheet in a secondary battery sheet using PTFE and has excellent strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram showing a cross-sectional view of a battery cell for measuring ion conductivity. DETAILED DESCRIPTION
[0037] The present disclosure is described in detail below.
[0038] The resistance value of the sheet may be increased in a mixture using PTFE as a binder. The present disclosure solves such a problem and provides a method for producing a sheet for a solid secondary battery that can obtain a sheet with a low resistance value.
[0039] In the mixture using PTFE as a binder, the PTFE is fibrillated to thereby produce a function as a binder.
[0040] However, when PTFE and a conductive aid are mixed in the form of powder to manufacture electrodes, there is a situation of high resistance of the electrode. It is speculated that this is due to the uneven presence of PTFE in the electrode, so the conductive path is not fully formed. And then, if the uneven presence of the component is produced in the electrode, it also becomes the reason for the reduction of the strength of the electrode. On the other hand, when mixing violently to eliminate the uneven presence, the fibrillation of PTFE occurs excessively, resulting in a reduction in flexibility and strength. Therefore, by using a binder that does not produce the uneven presence of PTFE and a conductive aid, such a problem can be solved. In addition, such a binder can also be used appropriately in the formation of the electrolyte layer of a solid secondary battery. The electrolyte layer is a layer formed of a thin layer without using an active material. In the case of carrying out the manufacture of such an electrolyte layer sheet, conductivity also becomes an important topic. Especially in the case of a solid-state battery, since there is no liquid medium, it is important for the electrolyte layer sheet to maintain appropriate conductivity, and for this reason, it is important to control the conductivity of the sheet.
[0041] The method for producing a solid secondary battery sheet disclosed herein is characterized in that a binder having polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and being a powder without an active material is used. It should be noted that this is hereinafter referred to as the first binder disclosed herein.
[0042] On the other hand, it is known that if the active material is mixed with PTFE and a conductive aid in advance, lithium is dissolved from the active material due to water in the liquid medium, and the active material deteriorates, thereby causing problems such as reduced battery capacity and increased battery resistance (Patent Document 5). Therefore, by using a binder that does not contain an active material and is composed of a composition having PTFE and a conductive aid as essential components, the purpose of the present disclosure can be achieved without being limited by the active material.
[0043] In addition, when a mixed powder of polytetrafluoroethylene resin and Ketjen black or carbon nanotubes is used as a binder, it is preferred in terms of being able to reduce electrode resistance, and the use of such a binder can also achieve the purpose of the present disclosure. This effect cannot be obtained when other carbon-based conductive additives such as acetylene black are used. Such a binder is recorded as the second binder of the present disclosure.
[0044] The manufacturing method of the solid secondary battery sheet disclosed in the present invention is characterized in that a binder is used which is a composition composed of PTFE and a conductive aid as essential components and is a powder that does not contain active substances. That is, the particles constituting the powder are not only composed of PTFE and a conductive aid, but are composed of a composition containing both PTFE and a conductive aid. The manufacturing method of the solid secondary battery sheet disclosed in the present invention can use a mixed powder of polytetrafluoroethylene resin and Ketjen black or carbon nanotubes as a binder.
[0045] Hereinafter, such a binder and components blended in the binder will be described in detail.
[0046] (polytetrafluoroethylene resin)
[0047] In the present disclosure, the PTFE is not particularly limited and may be a homopolymer or a fibrillated copolymer, but a homopolymer is more preferred.
[0048] In the case of a copolymer, examples of the fluorine-containing monomer as a comonomer include chlorotrifluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroalkylethylene, fluoroalkyl / fluorovinyl ether and the like.
[0049] The standard specific gravity (SSG) of PTFE, which is a raw material when preparing the mixture of the present disclosure, is 2.200 or less. By setting the SSG within the above range, the electrode strength can also be improved.
[0050] The SSG is preferably 2.180 or less, more preferably 2.170 or less, further preferably 2.160 or less, still more preferably 2.150 or less, still more preferably 2.145 or less, and particularly preferably 2.140 or less.
[0051] The above-mentioned SSG is also preferably 2.130 or more.
[0052] Regarding the standard specific gravity [SSG], a sample was prepared in accordance with ASTM D-4895-89, and the specific gravity of the obtained sample was measured by a water displacement method.
[0053] The PTFE used in the present disclosure can have a core-shell structure. As the PTFE with a core-shell structure, for example, the polytetrafluoroethylene of the core that comprises high molecular weight polytetrafluoroethylene and the shell of polytetrafluoroethylene or modified polytetrafluoroethylene of lower molecular weight in the particle can be enumerated. As such polytetrafluoroethylene, for example, the polytetrafluoroethylene etc. recorded in writing in the Japanese Patent Table 2005-527652 communique can be enumerated.
[0054] The PTFE in powder form satisfying the above parameters can be obtained by an existing production method, for example, by the production method described in International Publication No. 2015-080291, International Publication No. 2012-086710, etc.
[0055] (Conductive additive)
[0056] As the above-mentioned conductive auxiliary agent, any known conductive material can be used. As a specific example, metal materials such as copper and nickel, graphite (graphite) such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, needle coke, carbon nanotubes, carbon nanohorns, carbon nanofibers, fullerene and graphene, carbon materials such as amorphous carbon such as VGCF, etc. can be cited. Acetylene black is particularly preferred. It should be noted that they can be used alone or in any combination and ratio. Examples of commercially available carbon black include TOKABLACK #4300, #4400, #4500, #5500, etc. (manufactured by Tokai Carbon Co., Ltd., furnace black), Printex L, etc. (manufactured by Degussa, furnace black), Raven 7000, 5750, 5250, 5000 ULTRA III, 5000 ULTRA, etc., Conductex SC ULTRA, Conductex 975 ULTRA, etc., PUER BLACK 100, 115, 205, etc. (manufactured by Columbia, furnace black), #2350, #2400B, #2600B, #30050B, #3030B, #3230B, #3350B, #3400B, #5400B, etc. (manufactured by Mitsubishi Chemical Corporation, furnace black), MONARCH 1400, 1300, 900, Vulcan XC-72R, Black Pearls2000, LITX-50, LITX-200, etc. (manufactured by Cabot, furnace black), Ensaco 250G, Ensaco 260G, Ensaco 350G, Super-P Li (manufactured by IMERYS, furnace black), Ketjen Black ECP, ECP-600JD, LIONITE CB, etc. (manufactured by Lion Specialty Chemicals, Ketjen Black), Denka Black HS-100, Li-100, FX-35 (manufactured by Denka Co., Ltd., acetylene black), etc. As commercially available VGCF, VGCF-H (manufactured by Showa Denko Co., Ltd.) and the like can be cited. As commercially available multilayer carbon nanotubes, FT7000 (manufactured by CNano) and the like can be cited. As multilayer carbon nanotubes, the average outer diameter is preferably 12nm to 7nm. The average fiber length is preferably 1μm to 20μm. Thus, good conductivity can be obtained.
[0057] When the composite sheet is produced, a conductive auxiliary agent may be further added and mixed for use.
[0058] The adhesive disclosed in the present invention preferably contains the conductive additive in a ratio of 1.0 to 60.0 mass relative to the total amount of the adhesive. Thus, good conductivity and sheet strength can be obtained. The lower limit is more preferably 1.5 or more, and more preferably 2.0 or more. The upper limit is more preferably 55.0 or more, and more preferably 50.0 or less.
[0059] In the present disclosure, the conductive auxiliary agent must be contained in the binder. However, when a composite sheet is produced using the composite, PTFE and a conductive auxiliary agent may be further added and used.
[0060] The conductive aid is preferably used in a manner that the content is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.8% by mass or more in the mixture, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less. If the content is below this range, the conductivity may be insufficient. On the contrary, if the content is above this range, the battery capacity may be reduced.
[0061] When mixing the conductive auxiliary agent and PTFE, materials that can be added as needed include conductive materials, dispersants, thickeners, etc. For example, celluloses such as carboxymethyl cellulose (CMC) and methyl cellulose (MC) can be preferably used as thickeners.
[0062] When using components other than these conductive additives and PTFE, the blending amount of such components is preferably 5.0 mass % or less relative to the total amount of the binder. If more than 5.0 mass % of the above other components are blended, the purpose of the present invention may not be fully achieved.
[0063] (Binder)
[0064] The binder used in the present disclosure is a binder in which a composition having PTFE and a conductive auxiliary agent as essential components is in a powdered form. That is, the composition in a state where PTFE and the conductive auxiliary agent are mixed is in a powdered form, and does not contain a mixture of the respective powders of PTFE powder and conductive auxiliary agent powder. Such a state is not particularly limited, and particles in a state of granulation by spray drying are particularly preferred.
[0065] The binder preferably contains PTFE and the conductive additive at a weight ratio of 99:1 to 50:50. Among the above mixing ratios, the weight ratio is preferably 95:5 to 60:40, and more preferably 90:10 to 65:35.
[0066] The manufacturing method of the above-mentioned binder is not particularly limited and can be manufactured by any method, wherein it is preferably manufactured by a manufacturing method having a step (A) of mixing PTFE and a conductive aid in the presence of a liquid medium. In this case, a method of adding a conductive aid as a powder to a liquid dispersion of PTFE and mixing, a method of mixing a liquid dispersion of PTFE with a liquid dispersion of a conductive aid, etc. can be enumerated.
[0067] The mixing method may be carried out by a general method, for example, a dispersing machine, a homomixer, a mixer such as a planetary mixer, a homogenizer, a wet jet mill, etc., but the invention is not limited thereto.
[0068] In the above step (A), a dispersion having PTFE, a conductive aid and a liquid medium as essential components is used. The total amount of PTFE and the conductive aid in such a dispersion is preferably 1 wt % to 60 wt % relative to the total amount of PTFE, the conductive aid and the liquid medium. The above lower limit is more preferably 2 wt %, and more preferably 3 wt %. The above upper limit is more preferably 50 wt %, and more preferably 30 wt %.
[0069] Mixing them in a liquid medium is preferred because PTFE and the conductive additive can be mixed with high uniformity. The liquid medium in such mixing is preferably water.
[0070] In this case, it is preferable to use an aqueous dispersion of PTFE obtained by emulsion polymerization as the raw material.
[0071] The PTFE used as the raw material of the binder preferably has an average primary particle size of 100 nm to 350 nm because it can obtain a composite sheet with higher strength and excellent homogeneity. By making the average primary particle size within the above range, the molecular weight of the PTFE is high, and the binding force and flexibility of the electrode are improved.
[0072] The average primary particle size is more preferably 340 nm or less, further preferably 330 nm or less, still more preferably 300 nm or less, still more preferably 280 nm or less, and particularly preferably 250 nm or less, and is more preferably 150 nm or more, further preferably 170 nm or more, and still more preferably 200 nm or more.
[0073] The average primary particle size is measured by the following method.
[0074] The PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the 550nm projected light relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared. The calibration curve was used to determine the number average particle size from the measured transmittance of the 550nm projected light of each sample, which was used as the average primary particle size.
[0075] The mixture of PTFE and the conductive aid mixed in the liquid medium by the above-mentioned step (A) is preferably then dried by spray drying (step (B)) to remove the liquid medium. Drying methods include, for example, a rack dryer, a vacuum dryer, a freeze dryer, a hot air dryer, a drum dryer, a spray dryer, etc. Spray drying is particularly preferred. Spray drying is a method of spraying a mixture of a liquid and a solid into a gas to rapidly dry it and produce a dry powder.
[0076] Thus, a powdery binder in which PTFE and a conductive aid are uniformly mixed can be obtained. Spray drying is a generally known method and can be carried out in a usual manner using any known device. The above-mentioned step (B) can be carried out by a general method using a known general device. The drying temperature is preferably in the range of, for example, 100°C to 250°C. When it is above 100°C, the solvent can be fully removed, and when it is below 250°C, the energy consumption can be further reduced, which is preferred. The drying temperature is more preferably above 110°C, and more preferably below 220°C. In addition, the amount of liquid supplied also depends on the scale of production, for example, it can be in the range of 0.1L / hour to 2L / hour. In addition, the nozzle size for spraying the solution also depends on the scale of production, for example, it can be in the range of 0.5mm to 5mm in diameter.
[0077] The water content of the binder obtained in this way is preferably 1000 ppm or less.
[0078] By adjusting the water content to 1000 ppm or less, it is preferable from the viewpoint of being able to produce a secondary battery with less gas generation as an initial characteristic.
[0079] The water content is more preferably 500 ppm or less.
[0080] [Determination of water content]
[0081] Regarding the moisture content of the binder, a Karl Fischer moisture meter (ADP-511 / MKC-510N manufactured by Kyoto Electronics Industry Co., Ltd.) with a boat-type moisture vaporizer was used, and the vaporized moisture was measured by heating the moisture vaporizer to 210°C. As a carrier gas, nitrogen was circulated at a flow rate of 200 mL / min, and the measurement time was set to 30 minutes. In addition, Chem-Aqua was used as a Karl Fischer reagent. The sample amount was set to 1.5 g.
[0082] The second binder disclosed in the present invention is a mixed powder of polytetrafluoroethylene resin and Ketjen black and / or carbon nanotubes. When such a mixed powder is used as a binder, it is preferable to use a known carbon conductive additive such as acetylene black from the perspective of being able to reduce electrode resistance and improve battery characteristics, and can be used in the same manner as the first binder.
[0083] In the second binder, the Ketjen black and / or carbon nanotubes used are not particularly limited, and the above-mentioned ones can be used. Furthermore, the carbon nanotubes are preferably multilayered, and more specifically, preferably have an average fiber length of 1 μm to 20 μm.
[0084] The polytetrafluoroethylene used in the second binder may be the same as that used in the first binder.
[0085] The second binder may be obtained through the steps (A) and (B) in the same manner as the first binder, or may be obtained by simply mixing these components.
[0086] In the secondary battery sheet production composition and the like described in detail below, the first binder and the second binder can be used in the same manner.
[0087] (Composition for manufacturing secondary battery sheet)
[0088] The composition for making a secondary battery sheet refers to a composition containing all the components required for a secondary battery sheet. That is, it refers to a composition in which other components (electrode active materials, etc. in the case of electrodes) are mixed in the above-mentioned binder. In the case where the composition for making a secondary battery sheet is a composition for electrodes, it is a composition that contains electrode active materials, additional conductive additives, etc. in addition to the above-mentioned binder.
[0089] (Electrode Active Material)
[0090] As the above-mentioned positive electrode active material, there is no particular restriction as long as it can electrochemically encapsulate / release alkali metal ions, for example, preferably a material containing an alkali metal and at least one transition metal. As specific examples, transition metal composite oxides containing alkali metals, transition metal phosphate compounds containing alkali metals, conductive polymers, etc. can be cited.
[0091] Among them, as the positive electrode active material, a transition metal composite oxide containing an alkali metal that can generate a high voltage is particularly preferred. As the above-mentioned alkali metal ion, lithium ion, sodium ion, potassium ion, etc. can be cited. In a preferred embodiment, the alkali metal ion can be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0092] Examples of the alkali metal-containing transition metal composite oxide include
[0093] Formula: M a Mn 2-b M 1 b O4
[0094] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0.9≤a; 0≤b≤1.5; M 1 an alkali metal-manganese spinel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge,
[0095] Formula: MNi 1-c M 2 c O2
[0096] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤c≤0.5; M 2 an alkali metal-nickel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, or
[0097] Formula: MCo 1-d M 3 d O2
[0098] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤d≤0.5; M 3 The alkali metal-cobalt composite oxide is represented by at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge.
[0099] Among the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0100] Among them, MCoO2, MMnO2, MNiO2, MMn2O4, MNi 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., preferably a compound represented by the following general formula (3).
[0101] MNi h Co i Mn j M 5 k O2(3)
[0102] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, (h+i+j+k)=1.0, 0≤h≤1.0, 0≤i≤1.0, 0≤j≤1.5, 0≤k≤0.2.)
[0103] Examples of the alkali metal-containing transition metal phosphate compound include the following formula (4):
[0104] M e M 4 f (PO4) g (4)
[0105] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, 0.5≤e≤3, 1≤f≤2, 1≤g≤3). In the above, M is preferably a metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0106] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu and the like are preferred. Specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7; cobalt phosphates such as LiCoPO4; substances obtained by replacing a part of the transition metal atoms serving as the main body of these lithium transition metal phosphate compounds with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.; and the like.
[0107] The lithium-containing transition metal phosphate compound preferably has an olivine structure.
[0108] As other positive electrode active materials, MFePO4, MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2、MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3 (wherein M is at least one metal selected from the group consisting of Li, Na and K), etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 When the positive electrode active material such as O2 operates the secondary battery at a voltage exceeding 4.4V or a voltage above 4.6V, the crystal structure will not collapse, which is preferred from this aspect. Therefore, even when an electrochemical device such as a secondary battery using a positive electrode material containing the positive electrode active material exemplified above is stored at high temperature, the residual capacity is not easy to decrease, the resistance increase rate is not easy to change, and even if it operates at a high voltage, the battery performance will not deteriorate, so it is preferred.
[0109] Other positive electrode active materials include M2MnO3 and MM 6 O2 (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 6 Solid solution materials of transition metals such as Co, Ni, Mn, Fe, etc.
[0110] As the above-mentioned solid solution material, for example, a general formula M x [Mn (1-y) M 7 y ]O z Here, M in the formula is at least one metal selected from the group consisting of Li, Na and K, M 7It is composed of at least one metal element other than M and Mn, and for example, contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. In addition, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 A manganese-containing solid solution material such as Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O2, which is based on Li2MnO3 and in which LiNiO2 and LiCoO2 are solid-solved, can provide an alkali metal ion secondary battery with a high energy density, and is preferred in this regard.
[0111] In addition, if the positive electrode active material contains lithium phosphate, the continuous charging characteristics are improved, and thus it is preferred. The use of lithium phosphate is not limited, and it is preferred to use a mixture of the above positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and further preferably 0.5% by mass or more, based on the total lower limit of the above positive electrode active material and lithium phosphate, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 5% by mass or less.
[0112] Examples of the above conductive polymer include p-doped conductive polymers and n-doped conductive polymers. Examples of conductive polymers include polyacetylene-based, polystyrene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, and the like.
[0113] In addition, a substance having a different composition can be attached to the surface of the above positive electrode active material, and the positive electrode active material thus obtained can be used. Examples of the surface-attached substance include oxides such as alumina, silica, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.
[0114] These surface-attached substances can be attached to the surface of the positive electrode active material, for example, by the following methods: a method of dissolving or suspending in a solvent, infiltrating or adding to the positive electrode active material and drying; a method of dissolving or suspending a precursor of the surface-attached substance in a solvent, infiltrating or adding to the positive electrode active material, and then reacting it by heating or the like; a method of adding to the positive electrode active material precursor and firing simultaneously; and the like. It should be noted that in the case of attaching carbon, a method of mechanically attaching carbonaceous materials such as activated carbon can also be used.
[0115] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and further preferably 10 ppm or more, as the lower limit, and preferably 20% or less, more preferably 10% or less, and further preferably 5% or less, relative to the above-mentioned positive electrode active material, as the upper limit. The surface-attached substance can inhibit the oxidation reaction on the surface of the positive electrode active material and improve the battery life. If the amount of attachment is too small, the effect cannot be fully demonstrated; if the amount of attachment is too large, it will hinder the entry and exit of lithium ions, so the resistance may increase.
[0116] The shape of the particles of the positive electrode active material may be a block shape, a polyhedron shape, a sphere shape, an ellipsoidal sphere shape, a plate shape, a needle shape, a column shape, etc. The primary particles may be aggregated to form secondary particles.
[0117] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3 Above. If the tap density of the positive electrode active material is less than the above lower limit, the amount of conductive material and binder required when the positive electrode active material layer is formed will increase, and sometimes the filling rate of the positive electrode active material in the positive electrode active material layer will be limited, and the battery capacity will be limited. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density is, the better, and there is no particular upper limit. However, if it is too large, the density is difficult to compact during pressing, and sometimes the load characteristics are easily reduced. Therefore, the upper limit is preferably 4.0g / cm 3 Below, more preferably 3.7 g / cm 3 Below, more preferably 3.5 g / cm 3 the following.
[0118] It should be noted that in the present disclosure, the tap density is the powder packing density (tap density) g / cm2 when 5 g to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and vibrated 200 times with a stroke of about 20 mm. 3 Find out.
[0119] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter in the case where the primary particles are agglomerated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, further preferably 0.8 μm or more, most preferably 1.0 μm or more, and preferably 30 μm or less, more preferably 27 μm or less, further preferably 25 μm or less, and most preferably 22 μm or less. If it is less than the above lower limit, a high tap density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, so problems such as reduced battery performance will occur. Here, by mixing two or more of the above-mentioned positive electrode active materials with different median diameters d50, the filling property during positive electrode production can be further improved.
[0120] It should be noted that in the present disclosure, the median diameter d50 is measured using a known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as a dispersion medium used during measurement, a 0.1% by mass sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the measured refractive index is set to 1.24 for measurement.
[0121] In the case where the primary particles are agglomerated to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, further preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics is sometimes increased. On the contrary, if it is lower than the lower limit, crystallization is usually not developed, so problems such as poor reversibility of charge and discharge may occur.
[0122] It should be noted that in the present disclosure, the average primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph with a magnification of 10,000 times, for any 50 primary particles, the longest value of the slice intercepted by the left and right boundaries of the primary particles on a straight line in the horizontal direction is obtained, and the average value is taken to obtain the primary particle size.
[0123] The BET specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2If the BET specific surface area is smaller than this range, the battery performance is likely to decrease; if the BET specific surface area is larger than this range, it is difficult to increase the tap density.
[0124] It should be noted that in the present disclosure, the BET specific surface area is defined as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.), the sample is pre-dried at 150°C for 30 minutes under nitrogen flow, and then a nitrogen-helium mixed gas accurately adjusted to a relative pressure value of 0.3 relative to atmospheric pressure is used to measure the sample by the nitrogen adsorption BET single-point method based on the gas flow method, and the obtained value is used to define the BET specific surface area.
[0125] When the secondary battery of the present disclosure is used as a large lithium ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so the particles of the positive electrode active material preferably mainly contain secondary particles.
[0126] The particles of the positive electrode active material preferably have an average particle size of 40 μm or less for the secondary particles, and contain 0.5% to 7.0% by volume of microparticles having an average primary particle size of 1 μm or less. By containing microparticles having an average primary particle size of 1 μm or less, the contact area with the electrolyte becomes larger, which can further accelerate the diffusion of lithium ions between the active material and the electrolyte, and as a result, the output performance of the battery can be improved.
[0127] As a method for manufacturing positive electrode active materials, a common method for manufacturing inorganic compounds is used. In particular, various methods are considered for making spherical or ellipsoidal active materials, for example, the following methods can be cited: dissolving or crushing the raw material of the transition metal and dispersing it in a solvent such as water, adjusting the pH under stirring, making a spherical precursor and recovering it, drying it as needed, then adding LiOH, Li2CO3, LiNO3 and other Li sources and firing at high temperature to obtain the active material.
[0128] In order to manufacture the positive electrode, the above-mentioned positive electrode active materials can be used alone, or two or more of different compositions can be used together in any combination or ratio. As a preferred combination in this case, LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 O2 and other ternary combinations, LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced by other transition metals, or a combination of LiFePO4 and LiCoO2 or a portion of the Co is replaced by other transition metals, etc.
[0129] From the viewpoint of increasing the battery capacity, the content of the positive electrode active material in the positive electrode mixture is preferably 50% by mass to 99.5% by mass, and more preferably 80% by mass to 99% by mass.
[0130] In addition, the content of the positive electrode active material is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. In addition, the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode mixture is low, the capacitance is sometimes insufficient. On the contrary, if the content is too high, the strength of the positive electrode is sometimes insufficient.
[0131] The negative electrode active material is not particularly limited, and examples thereof include materials selected from lithium metal, artificial graphite, graphite carbon fiber, resin-fired carbon, pyrolysis vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-fired carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbon containing carbonaceous materials such as non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li4Ti5O 12 Among them, a substance containing at least a part of a carbonaceous material or a silicon-containing compound can be particularly preferably used.
[0132] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By containing silicon as a constituent element, a high-capacity battery can be produced.
[0133] As the material containing silicon, silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≤x≤1.6), or mixtures thereof are preferred. By using these substances, a negative electrode mixture for a lithium ion secondary battery having higher initial charge and discharge efficiency, high capacity, and excellent cycle characteristics is obtained.
[0134] Silicon oxide in the present invention is a general term for amorphous silicon oxides, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≤x≤1.6). x is preferably 0.8≤x<1.6, and more preferably 0.8≤x<1.3. The silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon and cooling and precipitating the generated silicon monoxide gas.
[0135] Particles having a structure in which silicon particles are dispersed in a silicon-based compound can be obtained, for example, by mixing silicon particles with a silicon-based compound and firing the mixture; or by heat treating silicon oxide particles before disproportionation represented by the general formula SiOx in an inactive, non-oxidizing atmosphere such as argon at a temperature of 400°C or more, preferably 800°C to 1,100°C, to perform a disproportionation reaction. In particular, the material obtained by the latter method is preferred because the silicon crystallites are uniformly dispersed. The above-mentioned disproportionation reaction can make the size of silicon nanoparticles 1nm to 100nm. It should be noted that the silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. It should be noted that the silicon nanoparticles (crystals) dispersed in the amorphous silicon oxide can be confirmed by transmission electron microscopy.
[0136] The physical properties of the particles containing silicon can be appropriately selected according to the target composite particles. For example, the average particle size is preferably 0.1 μm to 50 μm, and the lower limit is more preferably 0.2 μm or more, and further preferably 0.5 μm or more. The upper limit is more preferably 30 μm or less, and further preferably 20 μm or less. It should be noted that the average particle size in the present disclosure is expressed by the weight average particle size in the particle size distribution measurement based on the laser diffraction method.
[0137] The BET specific surface area of the silicon-containing particles is preferably 0.5 m 2 / g~100m 2 / g, more preferably 1m 2 / g~20m 2 / g. If the BET specific surface area is 0.5m 2 / g or more, there is no possibility of reduced adhesion when applied to the electrode and reduced battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and the battery capacity does not decrease when used as a negative electrode material for a lithium ion secondary battery.
[0138] By coating the silicon-containing particles with carbon to impart conductivity, it is observed that the battery characteristics are improved. As a method for imparting conductivity, there can be cited a method of mixing with conductive particles such as graphite, a method of coating the surface of the silicon-containing particles with a carbon film, and a method of combining the two. The method of coating with a carbon film is preferred, and as a coating method, a chemical vapor deposition (CVD) method is more preferred.
[0139] In order to increase the capacity of the obtained electrode mixture, the content of the above-mentioned negative electrode active material is preferably more than 40 mass %, more preferably more than 50 mass %, and particularly preferably more than 60 mass % in the electrode mixture. In addition, the upper limit is preferably below 99 mass %, more preferably below 98 mass %.
[0140] (Other ingredients)
[0141] The above-mentioned secondary battery sheet production composition may further contain a thermoplastic resin. Examples of the thermoplastic resin include vinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, and polyethylene oxide. One type may be used alone, or two or more types may be used in any combination and ratio.
[0142] Thermoplastic resin is generally more than 0.01 mass %, preferably more than 0.05 mass %, more preferably more than 0.10 mass %, and generally below 3.0 mass %, preferably below 2.5 mass %, more preferably below 2.0 mass %.By adding thermoplastic resin, the mechanical strength of electrode can be improved.In addition, if it exceeds this scope, the ratio of electrode active material in electrode mixture is reduced, and sometimes the problem of the capacity reduction of battery or the problem of resistance increase between active material can be produced.
[0143] (Solid electrolyte)
[0144] The solid electrolyte used in the solid secondary battery mixture of the present disclosure may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, there is an advantage of flexibility.
[0145] As the above-mentioned sulfide-based solid electrolyte, there is no particular limitation, and it can be selected from Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 Si 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x Any one of S4, Li6PS5Cl, etc., or a mixture of two or more.
[0146] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery using lithium ions as a carrier, and is particularly preferred from the perspective of an electrochemical device having a high energy density.
[0147] The oxide-based solid electrolyte is preferably a compound containing oxygen atoms (O), having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation.
[0148] As specific examples of compounds, for example, Li xa La ya TiO3[xa=0.3~0.7, ya=0.3~0.7](LLT), Li xb La yb Zr zb Mb mb O nb (Mbb is at least one element selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20), Li xc B yc Mcc zc O nc (Mcc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, xc satisfies 0≤xc≤5, yc satisfies 0≤yc≤1, zc satisfies 0≤zc≤1, and nc satisfies 0≤nc≤6), Li xd (Al,Ga) yd (Ti,Ge) zd Si ad P md O nd (where 1≤xd≤3, 0≤yd≤ 2 , 0≤zd≤2, 0≤ad≤ 2 , 1≤md≤7, 3≤nd≤15), Li (3-2xe) Mee xe DeeO (xe represents a number greater than 0 and less than 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms), Li xf Si yf O zf (1≤xf≤5,0 <yf≤3,1≤zf≤10)、Li xg S yg O zg (1≤xg≤3,0 <yg≤2,1≤zg≤10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 、Li3PO (4-3 / 2w) Nw (w satisfies w<1), Li with LISICON (lithium superion conductor) type crystal structure 3.5 Zn 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 ,La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ion conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh Si yh P 3-yh O 12 (where 0≤xh≤1, 0≤yh≤1), Li7La3Zr2O with garnet crystal structure 12 (LLZ), etc. In addition, ceramic materials in which LLZ is replaced by elements are also known. For example, LLZ-based ceramic materials in which LLZ is replaced by at least one element of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) can also be cited. In addition, phosphorus compounds containing Li, P, and O are also preferred. For example, lithium phosphate (Li3PO4), LiPON in which part of the oxygen in lithium phosphate is replaced by nitrogen, and LiPOD 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc.) and the like.
[0149] Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li2O-Al2O3-SiO2-P2O5-TiO2, etc.
[0150] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in solid-state batteries using lithium ions as carriers, and is particularly preferred from the perspective of electrochemical devices having high energy density.
[0151] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. In terms of good Li ion conductivity, an oxide having a crystalline structure is particularly preferred.
[0152] Examples of oxides having a crystal structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, etc.), garnet type (Li7La3Zr2O 12 (LLZ) etc. Among them, NASICON type is preferred.
[0153] The volume average particle size of the oxide-based solid electrolyte is not particularly limited, and is preferably 0.01 μm or more, and more preferably 0.03 μm or more. As an upper limit, it is preferably 100 μm or less, and more preferably 50 μm or less. It should be noted that the average particle size of the oxide-based solid electrolyte particles is measured in the following order. The oxide-based solid electrolyte particles are diluted with water (heptane in the case of substances unstable to water) in a 20 ml sample bottle to adjust to a dispersion of 1% by mass. The diluted dispersed sample is irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample, a laser diffraction / scattering particle size distribution measuring device LA-920 (manufactured by HORIBA) is used to obtain data 50 times at a temperature of 25 ° C using a measuring quartz dish to obtain the volume average particle size. Other detailed conditions, etc., are described in JIS Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are prepared for each level, and their average value is adopted.
[0154] The solid-state secondary battery mixture disclosed in the present invention is particularly suitable for lithium-ion solid-state secondary batteries.
[0155] In addition, it is suitable for sulfide-based solid-state secondary batteries.
[0156] When used in a solid-state secondary battery, the solid-state secondary battery mixture of the present disclosure is usually used in a sheet form.
[0157] The solid secondary battery composite sheet disclosed in the present invention can be a positive electrode sheet or a negative electrode sheet. In addition, it can also be made into a solid electrolyte layer sheet. Among these, when it is made into an electrode sheet, it further contains active material particles. The active material particles can be made into positive electrode active materials and negative electrode active materials. The solid secondary battery sheet disclosed in the present invention can be more suitable for use as a positive electrode sheet using a positive electrode active material. In addition, when it is made into an electrode sheet, it can contain a conductive auxiliary agent as needed.
[0158] (Method for manufacturing electrode)
[0159] The manufacturing method of the electrode disclosed in the present invention preferably uses a composition for making a secondary battery sheet obtained by mixing the above-mentioned components, and forms it into a sheet. In the sheeting, in order to omit the drying process, it is preferably carried out by reducing the amount of liquid medium or not using it at all, not preparing slurry, and applying shear stress to the composition for making a secondary battery sheet as a powder. In addition, in order to reduce the load of the device, a small amount of solvent can also be added as a lubricant. The solvent is preferably an organic solvent, and the amount of solvent contained is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less, relative to the composition for making a secondary battery sheet. As the lower limit of the above-mentioned amount of solvent contained, there is no special limitation, and it is preferably 0.5% by mass or more.
[0160] As the solvent, for example, N-methyl-2-pyrrolidone, butyl butyrate, acetone, etc., which dissolve the thermoplastic resin in the electrode mixture, can be cited. In addition, carbonates, ether compounds, and ionic liquids that can be used as components in the electrolyte can be cited. In particular, low-polarity solvents such as butyl butyrate and heptane are preferred from the aspect that the solid electrolyte performance will not be reduced.
[0161] It is known that if shearing force is applied to PTFE in powder state, it is easy to fibrillate. Utilizing this fibrillated property, PTFE can be used as a binder. That is, by entanglement of fibrillated PTFE with other powder components, the powder components are bonded, and thus PTFE can play a role as a binder when the powder components are molded.
[0162] It should be noted that, even when using fibrillated PTFE as a binding agent, if fibrillation is insufficient, good performance can not be brought into play when used as electrode mixture.Preferably, by having the fine fibrillation processing of the fibrous structure being more than 20nm with fibrillated diameter, fibrillated PTFE can bring into play good performance as the binding agent used for electrode mixture.
[0163] In the solid secondary battery sheet obtained by the manufacturing method disclosed herein, it is preferred to have PTFE as a constituent element, and the PTFE has a fibrous structure with a fibril diameter of more than 20nm. In the present disclosure, the fibril diameter (central value) (hereinafter, abbreviated as "fibril diameter") is preferably more than 20nm. That is, in this way, there is a PTFE with a thin fibril diameter in the electrode, which plays the role and flexibility of the powders constituting the components of the electrode being bonded to each other, and it is preferred from this aspect.
[0164] The fibril diameter is a value measured by the following method.
[0165] (1) Using a scanning electron microscope (S-4800, manufactured by Hitachi, Ltd.), a magnified photograph (7000 times) of the electrode mixture sheet was taken to obtain an image.
[0166] (2) Draw two lines at equal intervals horizontally on the image to divide the image into three equal parts.
[0167] (3) For all PTFE fibers located on the upper straight line, measure the diameter of each PTFE fiber at three locations, and take the average value as the diameter of the PTFE fiber. The three locations to be measured are the intersection of the PTFE fiber and the straight line, and the locations offset 0.5 μm upward and downward from the intersection. (Not including unfiberized PTFE primary particles).
[0168] (4) The above-mentioned operation (3) is performed on all PTFE fibers located on the lower straight line.
[0169] (5) Starting from the first image, move 1 mm to the right of the screen and take another photo, and measure the diameter of the PTFE fiber using the above (3) and (4). Repeat this operation until the number of measured fibers exceeds 80.
[0170] (6) The median value of the diameters of all the PTFE fibers measured above is taken as the fibril diameter.
[0171] The fibril diameter is preferably more than 15 nm, preferably more than 20 nm, more preferably more than 31 nm. If excessive fibrillation is performed, there is a tendency to lose flexibility. In addition, the upper limit is not particularly limited, and from the aspect of flexibility, for example, is preferably less than 150 nm, more preferably less than 100 nm, and particularly preferably less than 75 nm.
[0172] The method for obtaining PTFE having the above fibril diameter is not particularly limited, and an example thereof includes a method of performing the following steps:
[0173] Step (2), mixing the secondary battery sheet manufacturing composition while applying shear force to obtain an electrode mixture;
[0174] Step (3), forming the electrode mixture obtained in the above step (2) into a block; and
[0175] Step (4) is to roll the block-shaped electrode mixture obtained in the above step (3) into a sheet.
[0176] The above step (2) is a step of applying shear force while mixing the secondary battery sheet composition obtained in the above step (1) to obtain an electrode mixture. It should be noted that the powder components used to prepare the secondary battery sheet composition can also be mixed, and shear force can be applied while mixing to fibrillate the PTFE to prepare a mixture.
[0177] In this method, for example, by setting the mixing condition of the secondary battery sheet composition to 2000 rpm or less in step (2), PTFE can be fibrillated while maintaining flexibility, and by controlling the applied shear stress, the fibril diameter of PTFE can be set to 20 nm or more.
[0178] As described above, the amount of solvent contained in the secondary battery sheet-making composition in the step (2) is preferably 10% by mass or less. If the amount of solvent contained is 10% by mass or less, the drying step can be omitted, and productivity is improved, which is preferred.
[0179] Furthermore, it is also preferable to have a step (5) after the step (4) in which a greater load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also preferable to repeat the step (5).
[0180] In addition, after step (4) or step (5), the diameter of the original fibers can also be adjusted by having step (6), which is: the obtained calendered sheet is roughly crushed and then re-molded into a block shape, and calendered into a sheet shape. Step (6) is preferably repeated, for example, once or more and 12 times or less.
[0181] That is, by applying shear force, the PTFE powder is fibrillated and entangled with powder components such as active materials, thereby producing a mixture. It should be noted that the production method is described below.
[0182] In the manufacture method of the solid secondary battery sheet disclosed herein, the content of PTFE is usually more than 0.1 mass %, preferably more than 0.3 mass %, more preferably more than 0.5 mass %, in terms of the ratio of PTFE in the electrode mixture, and is usually less than 50 mass %, preferably less than 10 mass %, more preferably less than 5 mass %, and most preferably less than 0.9 mass %. If the ratio of PTFE is too low, active material cannot be fully maintained sometimes, and the mechanical strength of the electrode is insufficient, which can deteriorate battery performance such as cycle characteristics. On the other hand, if the ratio of PTFE is too high, the reduction of battery capacity and conductivity can be caused sometimes. It should be noted that in the manufacture method described in detail below, the situation using the first binder and the situation using the second binder can all be used in the same manner.
[0183] The electrode mixture disclosed herein can be used as an electrode mixture for a secondary battery, and is particularly suitable for a lithium-ion secondary battery.
[0184] When used in a secondary battery, the electrode mixture of the present disclosure is usually used in the form of a sheet.
[0185] An example of a specific method for producing an electrode mixture sheet including an electrode mixture is described below.
[0186] In the electrode manufacturing method disclosed in the present invention, the composite sheet can be obtained by a manufacturing method of a composite sheet for a secondary battery having the following steps:
[0187] Step (0), preparing a mixture containing an electrode active material and, if necessary, a conductive auxiliary agent;
[0188] Step (1), preparing a composition for manufacturing a secondary battery sheet containing a binder in the mixture obtained in the above step (0);
[0189] Step (2), mixing the secondary battery sheet manufacturing composition while applying shear force to obtain an electrode mixture;
[0190] Step (3), forming the mixture obtained in the above step (2) into a block; and
[0191] Step (4) is to roll the block-shaped mixture obtained in the above step (3) into a sheet-shaped form.
[0192] In the step (2) of applying shear force while mixing the secondary battery sheet composition, the electrode active material, the binder, etc. are simply mixed and exist in a state without a fixed shape. As a specific mixing method, there can be cited a method of mixing using a W-type mixer, a V-type mixer, a drum mixer, a ribbon mixer, a conical screw mixer, a single screw mixer, a twin screw mixer, a mill, a stirring mixer, a planetary mixer, etc.
[0193] In the above-mentioned step (2), the mixing conditions only need to set the rotation speed and mixing time appropriately. For example, the rotation speed is preferably below 2200rpm. It is preferably above 10rpm, more preferably above 15rpm, and further preferably above 20rpm. In addition, it is preferably below 2000rpm, more preferably below 1800rpm, and further preferably in the range of 1500rpm. If it is lower than the above-mentioned range, mixing takes time and productivity is affected. In addition, if it exceeds the above-mentioned range, fibrillation is excessively performed, and it is possible to become an electrode mixture sheet with poor strength and flexibility.
[0194] In the above step (3), forming into a block shape means forming the secondary battery sheet-making composition into one block.
[0195] Specific examples of the method for forming the block include extrusion molding, press molding, and the like.
[0196] In addition, the so-called "block-shaped" is not a particularly specific shape, as long as it is in a block-shaped state, including rod-shaped, sheet-shaped, spherical, cubic and other forms. The size of the block is preferably such that the diameter of the cross section or the smallest side is 10000 μm or more, and more preferably 20000 μm or more.
[0197] As a specific rolling method in the above step (4), there can be mentioned a method of rolling using a roll press, a flat plate press, a calender roll machine or the like.
[0198] In addition, after step (4), it is also preferred to have step (5): applying a greater load to the obtained calendered sheet to calender it into a thinner sheet. It is also preferred to repeat step (5). In this way, the calendered sheet is not thinned all at once, but is calendered little by little in stages, thereby making the softness better.
[0199] The number of times of performing step (5) is preferably 2 to 10 times, and more preferably 3 to 9 times.
[0200] As a specific calendering method, for example, the following method can be cited: two or more rollers are rotated, and a calender sheet is passed therebetween, thereby processing into a thinner sheet. Preferably, heating is performed during calendering. The lower limit of the temperature range is preferably above 40 degrees, more preferably above 50 degrees, and more preferably above 60 degrees. In addition, the upper limit is preferably below 300 degrees, more preferably below 250 degrees, and more preferably below 200 degrees. By heating, the sheet softens and can be easily calendered.
[0201] In addition, from the perspective of adjusting the diameter of the fibrils, it is also preferred to have a step (6) after the step (4) or the step (5): the rolled sheet is roughly crushed and then re-molded into a block shape, and rolled into a sheet shape. It is also preferred to repeat the step (6). The number of times of the step (6) is preferably 1 to 12 times, and more preferably 2 to 11 times.
[0202] In step (6), as a specific method for roughly crushing the calendered sheet and forming it into a block, there can be cited a method of folding the calendered sheet, a method of forming it into a rod or a film sheet, a method of forming it into a chip, etc. In the present disclosure, "roughly crushing" means changing the shape of the calendered sheet obtained in step (4) or step (5) into another shape in order to calender it into a sheet in the next step, and also includes the case of simply folding the calendered sheet.
[0203] In addition, step (5) may be performed after step (6), or the steps may be performed repeatedly.
[0204] Furthermore, uniaxial stretching or biaxial stretching may be performed in step (3) or (4), (5) or (6).
[0205] In addition, the fibril diameter can also be adjusted by adjusting the degree of pulverization in step (6).
[0206] In the above steps (4), (5) or (6), the calendering rate is preferably 10% or more, more preferably 20% or more, and preferably 80% or less, more preferably 65% or less, and more preferably 50% or less. If it is less than the above range, it takes time as the number of calendering increases, which affects productivity. In addition, if it exceeds the above range, fibrillation is excessively performed, which may result in a composite sheet with poor strength and flexibility.
[0207] It should be noted that the rolling rate mentioned here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before rolling. The sample before rolling can be a block-shaped secondary battery sheet composition or a sheet-shaped composition. The thickness of the sample refers to the thickness in the direction of the load applied during rolling.
[0208] As mentioned above, PTFE powder is fibrillated by applying shearing force. And, in order to have the fibrous structure that fibrillation diameter is more than 20nm, excessive shearing stress can excessively promote fibrillation, sometimes impairs flexibility. In addition, in terms of intensity, weak shearing stress is sometimes insufficient. Therefore, when mixing or calendering, by appropriately applying shearing stress to PTFE in the above-mentioned scope to promote fibrillation, calendering resin and extend into the operation of lamellar, it is possible to have the fibrous structure that fibrillation diameter is more than 20nm.
[0209] The composite sheet disclosed herein can be used as a composite sheet for a secondary battery. It can be made into either a negative electrode or a positive electrode. In particular, the composite sheet disclosed herein is suitable for a lithium ion secondary battery.
[0210] (positive electrode)
[0211] In the present disclosure, the positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the above-mentioned positive electrode active material.
[0212] Examples of the material of the positive electrode current collector include metals such as aluminum, titanium, tantalum, stainless steel, nickel, or alloys thereof, and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or alloys thereof, are preferred.
[0213] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate net, stamping metal, foamed metal, etc. can be enumerated, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be enumerated. Among these, metal foil is preferred. It should be noted that metal foil can be suitably formed into a mesh.
[0214] The thickness of the metal foil is arbitrary, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handling property is sometimes impaired.
[0215] In addition, from the perspective of reducing the electrical contact resistance between the current collector and the positive electrode mixture sheet, it is also preferred that a conductive auxiliary agent is coated on the surface of the current collector. Examples of the conductive auxiliary agent include carbon or precious metals such as gold, platinum, and silver.
[0216] The ratio of the thickness of the current collector to the positive electrode mixture sheet is not particularly limited, and the value of (the thickness of the positive electrode mixture sheet on one side) / (the thickness of the current collector) is preferably less than 20, more preferably less than 15, and most preferably less than 10. In addition, it is preferably more than 0.5, more preferably more than 0.8, and most preferably more than 1. If it exceeds this range, the current collector sometimes generates heat caused by Joule heat during charging and discharging at high current density. If it is less than this range, the volume ratio of the current collector to the positive electrode active material increases, and the capacity of the battery sometimes decreases.
[0217] The positive electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and vacuum dried.
[0218] From the perspective of high output and improved stability at high temperatures, the area of the positive electrode mixture sheet is preferably larger than the outer surface area of the battery case. Specifically, relative to the surface area of the outer packaging of the secondary battery, the sum of the electrode mixture areas of the positive electrode is preferably 15 times or more in terms of area ratio, and more preferably 40 times or more. Regarding the outer surface area of the battery case, in the case of a square shape with a bottom, it refers to the total area calculated by the length, width and thickness dimensions of the shell part filled with the power generation element except the protruding portion of the terminal. In the case of a cylindrical shape with a bottom, it refers to the geometric surface area of the shell part filled with the power generation element except the protruding portion of the terminal. The sum of the electrode mixture areas of the positive electrode refers to the geometric surface area of the positive electrode mixture layer facing the mixture layer containing the negative electrode active material. In a structure where a positive electrode mixture layer is formed on both sides by a collector foil, it refers to the sum of the areas calculated for each face.
[0219] The thickness of the positive electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite sheet after deducting the thickness of the collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit relative to a single side of the collector. In addition, the upper limit is preferably 500 μm or less, more preferably 450 μm or less.
[0220] In addition, a positive electrode having a substance having a different composition attached to the surface of the positive electrode may also be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.
[0221] (negative electrode)
[0222] In the present disclosure, the negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the above-mentioned negative electrode active material.
[0223] The material of the negative electrode current collector includes metals such as copper, nickel, titanium, tantalum, stainless steel, or alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials are preferred, and copper, nickel, or alloys thereof are particularly preferred.
[0224] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate net, stamping metal, foamed metal, etc. can be enumerated, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be enumerated. Among these, metal foil is preferred. It should be noted that metal foil can be suitably formed into a mesh.
[0225] The thickness of the metal foil is arbitrary, usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handling property is sometimes impaired.
[0226] The negative electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and then vacuum dried.
[0227] The density of the negative electrode mixture sheet is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More than, preferably 2.0 g / cm 3 Below, more preferably 1.9 g / cm 3 Below, more preferably 1.8 g / cm 3 If the range is exceeded, the charge-discharge characteristics under high current density are reduced, and sometimes high output cannot be obtained. In addition, if it is less than this range, the conductivity between the active materials is reduced, and sometimes the battery resistance increases and high output cannot be obtained.
[0228] The thickness of the negative electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite sheet after deducting the thickness of the collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit relative to a single side of the collector. In addition, the upper limit is preferably 500 μm or less, more preferably 450 μm or less.
[0229] (Element ratio of fluorine to carbon (F / C ratio))
[0230] The binder disclosed in the present invention preferably has an element ratio of fluorine to carbon (F / C ratio) of 0.40 to 3.00, more preferably 0.50 to 2.50. By being within such a range, an electrode with high strength and low electrode resistance can be manufactured, which is preferred from this aspect. It should be noted that the elemental analysis is a value measured using a common general method. Specifically, the F / C ratio can be measured simultaneously with CHN using MICRO CORDER JM10 (manufactured by J Science Lab) under the conditions of a sample amount of 2 mg, a combustion furnace of 950°C, a reduction furnace of 550°C, a helium flow rate of 200 mL / min, and an oxygen flow rate of 15 to 25 mL / min, and the average value of the values measured 4 times is obtained.
[0231] F / C ratio = average F (wt%) / average C (wt%)
[0232] (Solid-state secondary battery)
[0233] The present disclosure also relates to a solid-state secondary battery using the above-mentioned mixture sheet for a solid-state secondary battery.
[0234] The solid-state secondary battery of the present disclosure is more preferably an all-solid-state secondary battery.
[0235] The solid-state secondary battery is preferably a lithium-ion battery. In addition, the solid-state secondary battery is preferably a sulfide-based solid-state secondary battery.
[0236] The solid-state secondary battery is a solid-state secondary battery having a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, wherein the positive electrode and / or the negative electrode contain a positive electrode sheet and a negative electrode sheet as the solid-state secondary battery sheet disclosed above.
[0237] The above-mentioned solid electrolyte layer is obtained by molding the solid electrolyte into a sheet, and becomes an essential layer in making solid secondary batteries. The solid electrolyte sheet for forming such a solid electrolyte layer is not particularly limited, and any known solid electrolyte sheet can be used. In addition, it is also possible to use PTFE as a sheet obtained as a binding agent. Specifically, the composition containing PTFE resin and solid electrolyte can be used to be processed using the same method as the present disclosure, and PTFE is fibrillated and made into the material of the solid electrolyte sheet.
[0238] The laminated structure of a solid-state secondary battery using an electrode obtained by the method for manufacturing a solid-state secondary battery sheet disclosed in the present invention preferably comprises: a positive electrode comprising a positive electrode sheet and a positive electrode collector; a negative electrode comprising a negative electrode sheet and a negative electrode collector; and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode.
[0239] Hereinafter, the separator and the battery case used in the solid-state secondary battery of the present disclosure will be described in detail.
[0240] (Diaphragm)
[0241] The solid-state secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous films such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fiber.
[0242] (Battery Design)
[0243] The solid-state secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the positive electrode, negative electrode, sulfide-based solid-state battery electrolyte layer, etc. Specifically, cylindrical, square, button, laminated, etc. may be mentioned.
[0244] The solid-state secondary battery can be manufactured by, for example, firstly laminating the positive electrode, the solid electrolyte layer sheet, and the negative electrode in order and pressing them to manufacture the solid-state secondary battery.
[0245] By using the above-mentioned mixture sheet for solid secondary batteries, it is possible to produce a solid secondary battery with a low water content in the system, and it is possible to produce a solid secondary battery with good performance, which is preferable.
[0246] (Electrode mixture group share)
[0247] In a battery using electrodes manufactured using the method for manufacturing a solid-state secondary battery sheet disclosed herein, the proportion of the volume of the electrode mixture group in the battery internal volume (hereinafter referred to as the electrode mixture group occupancy rate) is generally greater than 40%, preferably greater than 50%, and is generally less than 90%, preferably less than 80%.
[0248] If the electrode mixture group occupancy rate is less than the above range, the battery capacity becomes smaller. In addition, if it exceeds the above range, there is less void space, the battery temperature rises, causing the components to expand or the vapor pressure of the liquid component of the electrolyte to increase, and the internal pressure to rise, which sometimes reduces the various characteristics of the battery such as the charge and discharge repetitive performance and high temperature storage, and then the gas release valve that releases the internal pressure to the outside works.
[0249] When the electrode mixture group is the above-mentioned laminated structure, it is preferred to use a structure formed by bundling the metal core parts of each electrode mixture layer and welding them to the terminal. When the area of a piece of electrode mixture becomes larger, since the internal resistance becomes larger, it is also preferred to set multiple terminals in the electrode mixture to reduce the resistance. When the electrode mixture group is the above-mentioned winding structure, multiple lead structures can be set in the positive electrode and the negative electrode respectively, and bundled on the terminal, thereby reducing the internal resistance.
[0250] The material of the housing is not particularly limited as long as it is a material that is stable to the electrolyte used. Specifically, metals such as nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminated film (laminated film) of resin and aluminum foil are used. From the perspective of lightweight, metals such as aluminum or aluminum alloy and laminated films are preferably used.
[0251] In the case of using metal, there can be mentioned a case in which metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed package structure; or a case in which the above metals are used to form a riveted structure through a resin gasket. In the case of using the above laminated film, there can be mentioned a case in which a sealed package structure is formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above resin layers. In particular, in the case of forming a sealed structure by thermally bonding the resin layers through the collector terminal, since the metal is bonded to the resin, it is preferred to use a resin having a polar group or a modified resin into which a polar group is introduced as the sandwiched resin.
[0252] The secondary battery of the present disclosure may have any shape, for example, cylindrical, square, laminated, button, large, etc. The shape and structure of the positive electrode, negative electrode, and separator may be changed according to the shape of each battery.
[0253] Example
[0254] The present disclosure will be described in detail below based on examples.
[0255] In the following examples, "part" and "%" mean "part by mass" and "mass %", respectively, unless otherwise specified.
[0256] [Production example 1]
[0257] Referring to Preparation Example 2 of International Publication No. 2015-080291, a PTFE aqueous dispersion (solid content: 31.2% by mass) PTFE-A was obtained. The standard specific gravity was 2.16 as a result of measurement.
[0258] [Production example 2]
[0259] Referring to Preparation Example 3 of International Publication No. 2015-080291, a PTFE aqueous dispersion (solid content 30.9 mass %) PTFE-B was obtained. The amount of fluorinated surfactant used was 3290 ppm relative to the final PTFE yield. The standard specific gravity was 2.15 as a result of measurement.
[0260] [Production example 3]
[0261] Referring to Preparation Example 1 of International Publication No. 2012 / 086710, an aqueous dispersion of modified PTFE, PTFE-C, was obtained. The polymer concentration of the obtained aqueous dispersion was 30.1% by mass, the average primary particle size was 0.18 μm, and the standard specific gravity was 2.16 as a result of measurement.
[0262] [Production example 4]
[0263] Referring to Preparation Example 1 of International Publication No. 2012-063622, an aqueous dispersion of PTFE particles, PTFE-D, was obtained. The standard specific gravity was 2.19.
[0264] Measure 0.25g of Li-100 (acetylene black) as a conductive aid, add ultrapure water as a solvent, use a mixer to stir at 2000rpm for 3 minutes to prepare a conductive aid dispersion. Afterwards, add 4.75g of aqueous dispersion PTFE-A in terms of solid content, further add ultrapure water, and adjust the concentration of the solid content. The final amount of solvent is 45g, and then stir for 1 hour with a mixing rotor to prepare a mixed solution. Afterwards, a spray dryer (manufactured by Tokyo Physical and Chemical Instruments Co., Ltd.) is used to obtain a dry powder (inlet temperature 140°C, air volume 0.60 cubic meters / minute, flow rate 5.5g / minute). Then vacuum drying (100°C, 8 hours) is performed to obtain a binder 1.
[0265] As shown in Table 1, the type and amount of the PTFE aqueous dispersion, the type and amount of the conductive additive, and the amount of the solvent were changed to obtain binders 2 to 11. FT7000 in Table 2 is (multi-walled carbon nanotube).
[0266] The water content of adhesives 1 to 11 was measured and found to be 250 PPM or less for all of them.
[0267] [Table 1]
[0268]
[0269] [Production example 5]
[0270] The aqueous dispersion PTFE-D obtained in Preparation Example 4 was diluted to a solid content concentration of 15%, and stirred quietly in a container equipped with a stirrer in the presence of nitric acid to coagulate the PTFE. The coagulated PTFE was separated and dried at 160° C. for 18 hours to obtain a powdery PTFE-E containing no conductive additive.
[0271] (Example 1)
[0272] <Preparation of Positive Electrode Composition>
[0273] The following operations were performed in an Ar atmosphere.
[0274] As the active material, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, sulfide-based solid electrolyte (30LiI·70(0.75Li2S·0.25P2S5)), Li-100 as a conductive aid, and binder 1 are placed in a container.
[0275] The composition of the charged materials was active material: electrolyte: total conductive aid: binder = 70:28:1:1. The mixture was stirred at 1500 rpm for 10 minutes using a mixer to obtain a mixture.
[0276] The prepared binder 1 was added to the container containing the mixture, and the mixture was stirred at 40 rpm for 2 hours using a kneader to obtain a mixed powder composition.
[0277] The obtained mixed powder composition was rolled several times between metal rolls arranged in parallel to produce a self-supporting electrode composite sheet. The temperature of the metal rolls was set at 80°C.
[0278] After that, the rolled sheet just obtained was folded in half and roughly crushed, and after being formed into a block again, it was rolled into a sheet using a metal roller on a hot plate heated to 80 degrees to promote fibrillation, and the above process was repeated 6 times. After that, the positive electrode mixture sheet was cut into 5cm×5cm, put into a roller press heated to 80 degrees, and a load of 10kN was applied to obtain a positive electrode mixture sheet with a thickness of 400μm.
[0279] [Evaluation of ion conductivity]
[0280] The solid electrolyte sheet prepared above was cut into a disc with a diameter of 13 mm, and the aluminum foil cut into a disc with a diameter of 14 mm was placed in contact with the solid electrolyte layer, and the spacer and gasket were assembled and placed in a stainless steel 2032 type button battery case. Figure 1As shown, a restraining pressure (screw tightening pressure: 8N) was applied from the outside of the button battery shell to make a battery cell for ion conductivity measurement. Specifically, after standing in a constant temperature bath at 30°C for 1 hour, an impedance analyzer manufactured by SOLARTRON was used to perform AC impedance measurement with a voltage amplitude of 5mV and a frequency of 1MHz to 1Hz. The resistance of the sample in the film thickness direction was thus obtained, and the ion conductivity was obtained by the following calculation formula.
[0281] Ionic conductivity (mS / cm) = 1000 × sample film thickness (cm) / (resistance (Ω) × sample area (cm 2 ))
[0282] [Strength measurement]
[0283] A tensile tester (Autograph AGS-X series AGS-100NX manufactured by Shimadzu Corporation) was used to measure the strength of each sample using a 10 mm wide strip of positive electrode mixture sheet test piece at 100 mm / min. The distance between the chucks was set to 30 mm. Displacement was given until fracture, and the maximum stress of the measurement result was used as the strength of each sample. Comparative Example 1 was set to 100 for comparison.
[0284] (Examples 2 to 11)
[0285] A positive electrode mixture sheet was obtained in the same manner as in Example 1 except that a binder having a composition shown in Table 1 was used.
[0286] (Examples 12 and 13)
[0287] Using the binder with the composition shown in Table 1, Li (Ni 0.6 Mn 0.2 Co 0.2 )O2, sulfide-based solid electrolyte (30LiI·70(0.75Li2S·0.25P2S5)), Li-100 as a conductive aid, and binder 2 or 10 are respectively put into the container.
[0288] The composition of the charged solution was active material: electrolyte: total conductive aid: binder = 70.6:28:0.7:0.7. The mixture was stirred at 1500 rpm for 10 minutes using a mixer to obtain a mixture.
[0289] (Comparative Example 1)
[0290] A positive electrode mixture sheet was obtained in the same manner as in Example 1 except that powdery PTFE-E containing no conductive additive was used.
[0291] [Table 2]
[0292]
[0293] The fibril diameters of Examples 5, 6, 7, 8, 10, 12, and 13 were measured, and the fibril diameters (median value) were 37 nm, 32 nm, 37 nm, 51 nm, 37 nm, 38 nm, and 33 nm, respectively.
[0294] It can be seen that compared with the examples, an electrode with high tensile strength and good ion conduction can be produced. If the tensile strength is high, the amount of added binder can be reduced and the amount of active material can be increased. From the above results, it is found that the battery characteristics can be improved by using a binder that is a powder that does not contain electrode active material.
[0295] Industrial Applicability
[0296] The solid-state secondary battery electrode obtained by the method for producing a solid-state secondary battery electrode disclosed herein can achieve low resistance of the electrode and can be suitably used in a solid-state secondary battery.
Claims
1. A method for manufacturing a sheet for a solid-state secondary battery, characterized in that: The process has the following steps: Step (1), using a binder which is a powder composed of a composition containing a polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and does not contain an active material, to prepare a composition for manufacturing a secondary battery sheet in the form of a powder; and Step (2), applying shear force while mixing the secondary battery sheet manufacturing composition to obtain an electrode mixture, The step (2) is performed under the condition that the amount of solvent contained in the secondary battery sheet-producing composition is 10% by mass or less.
2. The method for producing a sheet for a solid-state secondary battery according to claim 1, wherein: The content of polytetrafluoroethylene resin in the electrode mixture is 0.9 mass % or less.
3. The method for producing a sheet for a solid-state secondary battery according to claim 1 or 2, wherein: The moisture content of the binder is 1000 ppm or less.
4. The method for producing a sheet for a solid-state secondary battery according to any one of claims 1 to 3, wherein: The binder is produced by a production method including a step (A) of mixing a polytetrafluoroethylene resin and a conductive additive in the presence of a liquid medium.
5. The method for producing a sheet for a solid-state secondary battery according to claim 4, wherein: The liquid medium is water.
6. The method for producing a sheet for a solid-state secondary battery according to claim 4 or 5, wherein: The binder is obtained by a production method having a step (B) of drying the composition obtained in the step (A) by spray drying.
7. The method for producing a sheet for a solid-state secondary battery according to any one of claims 1 to 6, wherein: The standard specific gravity of the polytetrafluoroethylene resin is 2.130 to 2.
200.
8. The method for producing a sheet for a solid-state secondary battery according to any one of claims 1 to 7, wherein: The composition for manufacturing a secondary battery sheet includes a positive electrode active material.
9. The method for producing a sheet for a solid secondary battery according to any one of claims 1 to 8, wherein: The secondary battery is a lithium ion secondary battery.
10. The method for producing a sheet for a solid secondary battery according to any one of claims 1 to 9, wherein: The polytetrafluoroethylene resin has a fibrous structure in which the average median diameter of the fibril in the solid secondary battery sheet is 20 nm or more.
11. The method for producing a sheet for a solid secondary battery according to any one of claims 1 to 10, wherein: The binder has an element ratio of fluorine to carbon, that is, a F / C ratio, which is measured by elemental analysis and is 0.4 to 3.
0.
12. A binder for solid-state secondary battery electrodes, characterized in that: It is a powder composed of a composition having polytetrafluoroethylene resin and a conductive auxiliary agent as essential components and does not contain an electrode active material. The polytetrafluoroethylene resin and the conductive additive are contained in a weight ratio of 90:10 to 65:
35. 13 . The binder for solid secondary battery electrodes according to claim 12 , wherein the water content is 1000 ppm or less. 14 . The binder for solid secondary battery electrodes according to claim 12 , wherein the element ratio of fluorine to carbon (F / C ratio) measured by elemental analysis is 0.4 to 3.
0.
15. A binder for solid-state secondary battery electrodes, characterized in that: Contains a mixed powder of polytetrafluoroethylene resin and ketjen black and / or carbon nanotubes.
16. A composition for electrode preparation, characterized in that: Contains the binder for solid secondary battery electrodes according to claim 15.
17. An electrode mixture, characterized in that: Contains the binder for solid secondary battery electrodes according to claim 15.
18. An electrode, characterized in that: An electrode mixture according to claim 17.
Citation Information
Patent Citations
Production of powdery carbon black-ptfe uniform mixture
JP1994316784A
Concentrated Fluoropolymer Dispersion
JP2005527652A
Method for producing composite particle for electrode of electrochemical element
JP2008140809A
Dry electrode for energy storage device and its manufacturing method
JP2017517862A
Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2020115485A